The Effect of Psychological Empowerment on Employee Performance with Mediation Role of Job Satisfaction: Evidence from Egyptian Oil and Gas Sector - Adel, Ahmed; Ragheb, Mohamed A.; Ragab, Aiman Ahmed; Ahmed, Maha Hafez (The Arab Journal of Administration, 2025)
The goal of this research is to empirically investigate the effect PE(PE) on employee performance (EP) with Mediation Role of job satisfaction (JS)in the Egyptian oil and gas sector. The objectives of this research are: to investigate the relation among PE and employee performance, to test the relation among PE and job satisfaction, to investigate the relation among JS and employee performance, and to examine the mediation role of JS among PE and employee performance. The methodology used is focused on quantitative analysis utilizing an online survey tool to collect the necessary data and AMOS software for structural equation model analyses (SEM). The study’s findings revealed that: all the hypotheses are supported. Finally, the study found that there is a partial mediation effect of the JS among PE and EP in Egyptian oil and gas sector.